Optical Nonlinearity of Oxazine Dye Doped PMMA Films by Z-Scan Techniques - Jaffar, Amal Faisal (Al-Nahrain Journal of Science, 2018)
In this experimental work, a study (by using a high sensitive method known as Z-Scan technique) of the nonlinear optical properties for the laser dyes oxsazine in PMMA doped films with different concentrations with the solvent Chloroform.Z-scan experiment was performed using CW diode laser at 650 nm with the power output of 40 mW, in two parts. The first part was done using a closed-aperture placed in front of the detector to measure the nonlinear refractive index. In the second part; the aperture in front the detector was removed (open aperture) to measure the nonlinear absorption coefficient. The experimental results for closed aperture show that the dye doped films exhibits negative refractive index (self_defocusing) for the law concentrations (10-6 &10-5 M/L), while the large concentrations 10-4 &10-3 M/L had damaged. The results show also that the nonlinear refractive index and the third order nonlinear susceptibility increased with the increasing concentration. This is due to the increasing of the film thickness which caused an increase in the nonlinear phase shift in the samples. For open aperture z-scan the results show that the samples exhibited saturation absorption. The samples of law concentrations have a large nonlinear optical effect, which can be a promising candidate for photonic device application